The Relationship of Attitudes to Compliance with the Use of Personal Protective Equipment in the Construction Project of Hermina Hospital, Madiun City - Sri Wahyuni; Pipid Ari Wibowo; Zaenal Abidin (CV. Syntax Corporation Indonesia, 2024)
The construction industry is a dynamic field with potential hazards that can affect project quality and performance. Proper implementation of Occupational Safety and Health (OHS) management is essential in construction projects. The use of personal protective equipment (PPE) is an important aspect of OHS, but compliance among construction workers is still lacking. This study aims to determine the relationship between attitude and compliance with the use of PPE on the Hermina Hospital construction project in Madiun City. This study was a cross-sectional study, and data were collected using a questionnaire. This study involved 93 construction workers. The results showed that 62% of construction workers in Ethiopia did not use PPE while working, mainly due to lack of availability (41.1%), lack of orientation on the use of PPE (21.3%), discomfort (16.3%), and lack of perceived importance (1.3%). In Indonesia, approximately 60% of workers have experienced head injuries due to not wearing a safety helmet, 90% have experienced facial injuries due to not wearing a face shield, 77% have experienced foot injuries due to not wearing safety shoes, and 66% have experienced eye injuries due to not using eye protection. The low compliance with PPE use among construction workers is a significant concern, as this increases the risk of occupational injuries and accidents. Factors such as availability, training, comfort, and perceived importance of PPE should be addressed to improve compliance. Employers and policy makers need to prioritize the implementation of effective OHS management in construction projects to protect workers' health and safety.